2018
DOI: 10.1021/acs.est.7b04122
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Impacts by Fragments Released from Nanoenabled Products: A Multiassay, Multimaterial Exploration by the SUN Approach

Abstract: Nanoenabled products (NEPs) have numerous outdoor uses in construction, transportation or consumer scenarios, and there is evidence that their fragments are released in the environment at low rates. We hypothesized that the lower surface availability of NEPs fragment reduced their environmental effects with respect to pristine nanomaterials. This hypothesis was explored by testing fragments generated by intentional micronisation ("the SUN approach"; Nowack et al. Meeting the Needs for Released Nanomaterials Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 58 publications
3
38
0
Order By: Relevance
“…The findings strengthen the calls for more release and aging type of studies when Fig. 1 The UV-Vis spectra obtained from the analysis of SUN A, B and C extracts examining the environmental implications of ENMs from NEPs, as experimentally it has been demonstrated that the product matrix is often associated with released ENMs [1], and data drawn from studies with pristine ENMs is of poor value. Results obtained from TEM coupled with EDS also indicated the release of TiO 2 ENMs in both wastewater types (Fig.…”
Section: Releasesupporting
confidence: 62%
“…The findings strengthen the calls for more release and aging type of studies when Fig. 1 The UV-Vis spectra obtained from the analysis of SUN A, B and C extracts examining the environmental implications of ENMs from NEPs, as experimentally it has been demonstrated that the product matrix is often associated with released ENMs [1], and data drawn from studies with pristine ENMs is of poor value. Results obtained from TEM coupled with EDS also indicated the release of TiO 2 ENMs in both wastewater types (Fig.…”
Section: Releasesupporting
confidence: 62%
“…Based on these hydrodynamic diameter values, we expected that the aggregation and settling down of the CuO_Acryl_FP would be fast in the water column of the mesocosms. Such strong colloidal instability was also observed in artificial freshwater using FP of epoxy, polyolefin, polyoxymethylene, and cement containing nanoparticles 24 .…”
Section: Fast Aggregation and Sedimentation Of Cuo_acryl_fp In Volvicmentioning
confidence: 62%
“…The physical-chemical mechanism of hetero-aggregation of the CuO-NOAA at pH = 8.1 ± 0.1 is related to the electrostatic attraction between the positively charged CuO and the negatively charged clays (as the lateral charges of kaolinite 28 ) but also picoplankton (as bacteria, algae) 29 . CuO_Acryl_FP as others breakup/fragmented/released particles of plastics, cement, and paints 24,30,31 were found very instable as soon as they are put in suspension. Their aggregation in the water column of the mesoscosm was attributed to the large size of the FP (D 10 =20±4 μm, D 50 =73±29 μm and D 90 =190±86 μm) leading to their fast settling down (Figure 4).…”
Section: Surficial Sediments Concentrate the Pollutionmentioning
confidence: 99%
“…33 Further release analyses by mechanical shear (sonication) during immersion in water showed a high fragment release rate that was slightly reduced by embedded CNT fillers, 34 and where recently followed up by high-throughput ecotoxicity screening of the hazards of released fragments. 37 A high fragment release was also observed during leaching (7 d, ultrapure water, stirring) of photocatalytic cement nanocomposites (approx. 2.85 wt-% photocatalytic TiO 2 ).…”
Section: Introductionmentioning
confidence: 92%